THE ECONOMIC ESSENCE AND SPECIFIC FEATURES OF THE INVESTMENT ACTIVITIES OF INSURANCE ORGANIZATIONS (E Global Congress, 2025)
Insurance companies occupy a special place not only as important institutions ensuring financial stability, but also as active participants in the country’s economic system. One of their main functions is to ensure the financial security of the population and business entities through the provision of insurance services, while the second important area of activity is investment activity. Investment activity increases the financial stability of insurance companies, increases their income, and expands their ability to fulfill obligations on time. Therefore, an in-depth study of the scientific and theoretical foundations of investment activities carried out by insurance companies and the development of their methodological aspects is an urgent task.